Faisal Afandi RELEVANSI PENGGUNAAN ISTIHSAN DAN ISTISHAB DALAM KACAMATA EKONOMI SYARIAH - Faisal Afandi (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2022)
Ushul Fiqh is one of the important sciences that must be owned and mastered by everyone who wants to carry out the mechanism of ijtihad or istinbath Islamic law. Istihsan and istishab are two of the sources of Islamic law which are still disputed over their use. For those who refuse to use istihsan as a source of law because they think a mujtahid has taken something that he thinks is good, not based on arguments obtained directly according to the editors of the Qur’an and sunnah texts or based on the consent of the companions. Meanwhile, for those who use istihsan dan istishab as source of Islamic law, make them an alternative to determining the law when the agreed source cannot answer the problem. The purpose of this study is to analyze how the relevance of the use of istihsan dan istishab in the eyes of sharia economics. This research is a library research whose data is through library sources and other references related to istihsan dan istishab. The results of this study indicate that, (1) Istihsan is one istinbath methods that is very relevant to it’s use today because it prioritizes sharia maqasid and always tries to realize and maintain sharia maqasid, (2) Istishab is still very relevant to be applied as an alternative to solving legal cases in the fields of family law, criminal law, economics and civil law.